Developing a National Trauma Research Action Plan: Results from the postadmission critical care research gap Delphi survey. Issue 6 (2nd December 2022) - Brasel, Karen J.; Braverman, Maxwell A.; Phuong, Jimmy; Price, Michelle A.; Kaplan, Lewis J.; Kozar, Rosemary; Michetti, Christopher P.; Callcut, Rachael; Bulger, Eileen M.; ,; Callcut, Rachael; Codner, Panna; et al.
Abstract : As a part of the National Trauma Action Plan, a group of experts in surgical critical care have generated a research agenda in surgical critical care. Abstract : INTRODUCTION: The 2016 National Academies of Science, Engineering and Medicine report included a proposal to establish a National Trauma Research Action Plan. In response, the Department of Defense funded the Coalition for National Trauma Research to generate a comprehensive research agenda spanning the continuum of trauma and burn care from prehospital care to rehabilitation as part of an overall strategy to achieve zero preventable deaths and disability after injury. The Postadmission Critical Care Research panel was 1 of 11 panels constituted to develop this research agenda. METHODS: We recruited interdisciplinary experts in surgical critical care and recruited them to identify current gaps in clinical critical care research, generate research questions, and establish the priority of these questions using a consensus-driven Delphi survey approach. The first of four survey rounds asked participants to generate key research questions. On subsequent rounds, we asked survey participants to rank the priority of each research question on a 9-point Likert scale, categorized to represent low-, medium-, and high-priority items. Consensus was defined as ≥60% of panelists agreeing on the priority category. RESULTS: Twenty-five subject matter experts generated 595 questions. By Round 3, 249 questions reached ≥60% consensus. Of these, 22 questions were high, 185 were medium, and 42 were low priority. The clinical states of hypovolemic shock and delirium were most represented in the high-priority questions. Traumatic brain injury was the only specific injury pattern with a high-priority question. CONCLUSION: The National Trauma Research Action Plan critical care research panel identified 22 high-priority research questions, which, if answered, would reduce preventable death and disability after injury. LEVEL OF EVIDENCE: Diagnostic Tests or Criteria; Level IV. Abstract :